The effects of 8-week plyometric training on anaerobic power, balance and sprint performance of 12-14 aged female handball players - Pancar, Z.; Bicer, M.; Özdal, M. (Medicina dello Sport, 2020)
BACKGROUND: The effects of plyometric exercises on anaerobic performance are of great importance and have been recognized and started to be used in various sports. Its physiological effects on young athletes have mostly been investigated, but the effects on young budding sportsmen have rarely been a matter of concern. Therefore, the effects of plyometric exercises on anaerobic power, balance and sprint performance were investigated in children between 12-14 ages. METHODS: The aim of this study was to find out the effects of eight-week plyometrics training on women handball players` anaerobic power, balance and sprint performance. A total of 28 handball players, currently participating in the schools team, were included in the study. Handball players were divided as control (N.=14, age: 13.07±0.83) and experimental group (N.=14, age:13.07±0.83). Eight-week plyometrics training program together with handball training was carried out three times a week for the experimental group. On the other hand the control group continued their regular handball training. Before the study, their age, height, body weights were measured and noted down, and anaerobic power, balance and 30-meter sprint tests were applied. The isokinetic balance test for balance measurement and the Wingate test for anaerobic power were used. Paired Samples T test and Independent Samples T test were used to analyze the data. RESULTS: When the pre-test and post-test results of the experimental group were compared, statistically significant differences were found in their anaerobic power, balance and sprint measurements (P<0.05). There were no statistically significant differences between pre-test and post-test results in control group (P>0.05). As a result, between pre-test and post-test measurements of the groups; anaerobic power, balance and sprint values were found to be significant at P<0.05 in favor of the experimental group. CONCLUSIONS: It can be said that 8-week plyometric training has positive effects on anaerobic power, balance and sprint performance for female handball players between 12-14 years old.